The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s0004-282x2004000500034
|View full text |Cite
|
Sign up to set email alerts
|

Cefaléia numular: relato de caso

Abstract: RESUMO -A cefaléia numular (CN) ou cefaléia em forma de moeda (coin-shaped headache) foi descrita pela primeira vez por Pareja e colaboradores em 2002. É uma cefaléia de curso crônico, aparentemente primária, sendo a dor restrita a uma área circunscrita do crânio, cuja forma pode ser elíptica ou em moeda. Evolui ao longo do tempo com períodos de dor, intercalados por períodos assintomáticos. Na série de treze casos apresentada por esses autores ou não ocorreu concomitância com outras formas de cefaléias primár… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 5 publications
(4 reference statements)
0
8
0
1
Order By: Relevance
“…In a follow-up study (6), paracetamol has been shown to be beneficial as acute treatment. Gabapentin was an effective preventive therapy in two case reports (7, 8) and a case of NH was absolutely responsive to naproxen (9).…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up study (6), paracetamol has been shown to be beneficial as acute treatment. Gabapentin was an effective preventive therapy in two case reports (7, 8) and a case of NH was absolutely responsive to naproxen (9).…”
Section: Discussionmentioning
confidence: 99%
“…In NH patients with mild pain or only discomfort, treatment was either needless or analgesics and nonsteroidal antiinflammatory drugs usually sufficed. This seems to be also the experience of Monzillo et al, who described an NH case absolutely responsive to standard oral doses of naproxen 2 . However, patients suffering from moderate or even severe pain, required prophylactic treatment—including antimigrainous, antidepressant, and antiepileptic drugs—that proved to be generally unsatisfactory, except for isolated cases 3 .…”
mentioning
confidence: 59%
“…Since the original description in 2002 (1), reports of multiple cases have increased our clinical knowledge on NH (3–27). For example, we now know that the pain may be severe (3, 5, 13, 14, 17, 20, 24, 25), although it is usually mild or moderate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there could be a variable combination of sensory disturbances within the symptomatic area, including hypoaesthesia, paraesthesia, dysaesthesia and tenderness. However, since the first description of 13 patients in 2002, > 100 additional cases have been reported (3–27), some of which have shown different features, thus expanding the clinical spectrum of NH. Here we describe a new clinical feature in three patients, each presenting with focal head pain in two separate areas.…”
Section: Introductionmentioning
confidence: 99%